Sonate a tre - Ivančič, Amandus (Monumenta artis musicæ Sloveniæ, 1983)
Amandus Ivanschiz (in Slovenian literature "Ivančič"), due to his surname thought to be of South-Slave origin, belongs to a group of today little known 18th-century composers, but was in his own time all over Central Europe well known and largely copied monastic composer. Around 100 compositions survived to this date in various copies now preserved in Slovenian, Croatian, Austrian, Czech, etc. archives. However, only a few of his compositions are available to modern performers. Volume 1 of the Monumenta artis musicae Sloveniae series comprises five trio sonatas which are accompanied by an introductory presentation of the composer and his works and Revision Report by Damilo Pokorn (1983).The digitized version of the edition (2020) includes a New Introduction as well as Corrigenda by Maciej Jochymczyk bringing to the reader's attention new information on father Amandus and corrigenda of the earlier edition.